Centralization errors in comparative genomic hybridization array analysis of pituitary tumor samples. Issue 6 (9th March 2018) - Lasolle, Hélène; Alix, Eudeline; Bonnefille, Clément; Elsensohn, Mad‐Hélénie; Michel, Jessica; Sanlaville, Damien; Roy, Pascal; Raverot, Gérald; Bardel, Claire
Abstract: Reliable interpretation of comparative genomic hybridization array (aCGH) results requires centralization and normalization of the data. We evaluated the reliability of aCGH centralization by comparing aCGH results (with classical centralization‐normalization steps) to fluorescence in situ hybridization (FISH) results. In addition, we propose a method to correct centralization bias. Sixty‐six pituitary tumors were analyzed (Agilent aCGH + SNP 4 × 180K microarray). For each tumor, the FISH‐based log2 (ratios) of a subset of chromosomes were compared with the corresponding aCGH raw log2 (ratios). With our new normalization‐centralization process, this difference was added to all log2 (ratios), before performing loess regression on non‐altered probes only. Finally, the mean log2 (ratio) and the percentage of normal probes were compared between CGHnormaliter and our new FISH‐based method. For 11 tumors, FISH results and raw CGH log2 (ratios) differed significantly. In addition, nine tumors showed discrepancies between results generated by CGHnormaliter and our new‐method. Such discrepancies seemed to occur with tumours with many abnormalities (0%‐40% normal probes), rather than in those tumours with fewer abnormalities (31%‐100% normal probes). Five tumors had too few normal probes to allow normalization. In these tumors, which can exhibit many changes in DNA copy number, we found that centralization bias was frequent and uncorrected by current normalization methods. Therefore, an external control for centralization, such as FISH analysis, is required to insure reliable interpretation of aCGH data.